Effect of inhaled low molecular weight heparin on methacholine-induced bronchoconstriction - (:unkn) unknown (My University, 2000)
OBJECTIVES: Recent studies have shown that inhaled standard heparin exhibits protection towards various bronchoconstrictor stimuli in asthma including methacholine. Low molecular weight heparins (LMWH) (4000-5000 daltons) have higher bioavailability than standard heparins (12,000-16,000 daltons). It is possible that the anti-asthmatic activity of heparin may be molecular weight-dependent. The purpose of the present investigation was to study the effect of LMWH on methacholine-induced bronchoconstriction and to compare the effect of LMWH with that of standard heparin. SUBJECTS: Fifteen subjects (7 male, 8 female, mean age: 33 +/- 13 years, range: 20-65) with mild asthma were studied. METHOD: Methacholine bronchial provocation tests were performed in a single-blind, crossover, randomized order and repeated 45 minutes after placebo or aerosolized standard heparin (1.000 U/kg) or aerosolized LMWH (Enoksaparin, Clexane, 0.8 mg/kg). RESULTS: There was no significant difference in baseline FEV1 values between study days. The standard heparin and enoksaparin inhibited bronchoconstriction induced by methacholine. The geometric mean log PD20 values after placebo, standard heparin, and enoksaparin were 0.24 +/- 0.57 (1.74) mg/ml, 0.79 +/- 0.59 (6.17 mg/ml), 0.76 +/- 0.57 (5.75 mg/ml), respectively (p < 0.0009). Three subjects in standard heparin group and two subjects in enoksaparin group showed increased hyperreactivity, the others showed decreased bronchial hyperreactivity. The degree of protection offered by standard heparin and enoksaparin did not show any statistical difference. CONCLUSIONS: These data suggest that both inhaled LMWH and inhaled standard heparin play inhibitory roles in methacholine-induced bronchoconstriction.
Keywords: Adult; Female; Humans; Middle Aged; Aged; Male; Cross-Over Studies; Single-Blind Method; Administration, Inhalation; Methacholine Chloride; Bronchoconstriction; Heparin, Low-Molecular-Weight